Factors Associated with Occupational Sickness in Employess of PT. Virtue Dragon Nickel Industry - Hasda, Hasda; Azizi Jayadipraja, Erwin; Mendri, Ketut; Harun, Aziz (Magister Kesehatan Universitas Mandala Waluya, 2022)
Introduction: According to the Ministry of Energy and Mineral Resources, 24 processing and refining facilities are operating in Indonesia as of the end of 2017, consisting of 15 nickel smelters, 4 iron smelters, and 2 bauxite smelters, 2 manganese smelters, and 1 copper smelter. One of the nickel smelters that have been operating to date is PT. Dragon Virtue Industry located in Morosi Village, Kec. Morosi, Kab. Konawe. Method: This type of research is quantitative research with explanatory survey method, research that explains causality and hypothesis testing. located near 71 employees who visit and seek treatment at the health centers, a sample is taken from the formula so that a sample of 60 people is obtained. Result: From the results of the study, it is known that there is a relationship between Worker Age, Length of Work, Length of Work, and Use of Personal Protective Equipment with work-related events or diseases, where workers over 40 years of age can experience work-related illnesses. Conclusion: it can be concluded that there is a significant relationship between all variables and it is hoped that workers will have more self-protection by adjusting their abilities and age in doing work and for companies or industries they are expected to put more pressure on occupational health and safety officers to be more optimal in supervising workers in the company.